Considering cost alongside the effectiveness of management in evidence-based conservation: A systematic reporting protocol. (May 2017) - Cook, Carly N.; Pullin, Andrew S.; Sutherland, William J.; Stewart, Gavin B.; Carrasco, L. Roman
Abstract: Given the limited resources available to address conservation problems, decision-makers are increasingly seeking management solutions that provide value for money. Despite an increasing number of studies that generate estimates of the return-on-investment from conservation management interventions, the ways in which costs are reported are highly variable and generally aggregated. This prevents comparison between studies and the application of systematic tools to synthesize conservation evidence and evaluate the factors that modify costs and benefits. A standardised consensus on the type of cost data to collect and report in conservation science would help build a body of evidence to support decision makers. In efforts to improve evidence-informed decision-making, conservation has looked to health care for tools to support the integration of evidence into management decisions. Increasingly, health care uses economic evaluations of treatment options to estimate the return-on-investment from medical interventions. Here, we describe economic evaluations as a tool for evidence-informed decision-making in health care and draw parallels for how these evaluations could be integrated into conservation. We also suggest tools to help systematically report economic costs of conservation interventions, and illustrate this approach with a case study of turtle conservation. We describe the important elements of economic evaluations, and how these data can be used to greatest effect through tools for evidence synthesis, such as systematic reviews or synopses, to enable decision-makers to identify cost-effective interventions. We believe that a routine commitment from researchers to capture the costs of management interventions would help support evidence-informed decision-making by facilitating the economic evaluations that support cost-effective management decisions. However, this will require clear guidelines for how to capture these data and incentives for conducting the necessary economic evaluations. Being able to present results systematically as return-on-investment could be an important step in encouraging greater use of science by those making management decisions. Highlights: Studies of conservation interventions rarely report costs, or do so in a highly heterogeneous and generally aggregated manner. Poor cost reporting prevents comparison between studies and synthesis to evaluate the factors that modify costs and benefits. Economic evaluations from health care offer a template for how conservation studies could evaluate cost-effectiveness. We outline the critical elements of economic evaluations, and the metadata to report to contribute to a broader evidence base. We demonstrate a standardised protocol from health to report disaggregated cost data for a conservation case study. Conservation scientists and practitioners must commit to routinely reporting cost data to ensure cost-effective management.